Avaliação do impacto da cárie dentária na qualidade de vida relacionada à saúde em escolares de 12 anos - (:unkn) unknown (Universidade Federal do Amazonas, 2024)
Dental caries is a highly prevalent disease worldwide, which can affect daily life functions and cause psychological and social impairment, with the potential to negatively impact oral health-related quality of life (OHRQoL). The objective of the study was to evaluate the impact of caries on OHRQoL, considering the role of demographic and socioeconomic characteristics. An observational, longitudinal study was carried out, including 329 adolescents aged 12 years at the beginning of the follow-up, of both sexes, enrolled in the municipal schools in an urban area with unfavorable social indicators, in Manaus, Amazonas. Caries was assessed using the Decayed, Missing and Filled Teeth Index (DMFT) and OHRQoL was measured using the Child Perceptions Questionnaires instrument (CPQ11-14). Family income and parental schooling were also measured. Follow-up involved four times: T0 or baseline, 6 months (6M), 1 year (T1) and 2 years (T2) after baseline. At T0, all variables were measured. At 6M, only OHRQoL was measured. Caries and OHRQoL were measured at T1 and T2. Data analysis was carried out using structural equation modeling, with evaluation of the evolution in OHRQoL over the four periods of study, through a latent growth model, using the SPSS (Statistical Package for Social Sciences) and AMOS 22.0 programs. The greater number of decayed elements at baseline was associated with higher CPQ scores at baseline (β=0.131), and a greater number of teeth affected by caries in the period between one and two years of follow-up was associated with higher CPQ scores at two years (β=0.110). Being female was associated with greater increases (worsening) in the CPQ score throughout the follow-up period (β=0.212). Socioeconomic status was not associated with OHRQoL. It was concluded, therefore, that dental caries was a predictor of worse OHRQoL, both at the beginning and throughout the two-year follow-up. By including the assessment of symptoms and function and psychological, emotional and social aspects, in addition to physical aspects, OHRQOL allows the understanding of the perceived health status and the identification of needs not covered by oral health services.
Keywords: .; .; .; CIENCIAS DA SAUDE; Cárie dentária; Qualidade de vida; Estudos longitudinais